From local to a universal commitment to achieve the United Nations sustainable development goals - Vidal, Diogo Guedes (2020)
This essay is part of the MDPI Writing Prize, an annual award supported by MDPI Author Services, which provides services including language editing, reformatting, plagiarism checks. The winners of the 2020 MDPI Writing Prize about the theme “My work and the United Nations Sustainable Development Goals” are posted on Encyclopedia.